1971
DOI: 10.1128/jb.107.1.320-324.1971
|View full text |Cite
|
Sign up to set email alerts
|

Paracrystalline Sheets Reaggregated from Solubilized Exosporium of Bacillus cereus

Abstract: Fragments of exosporium, isolated from dormant spores of Bacillus cereus, were disintegrated by treatment with sodium dodecyl sulfate (SDS) or with phenol and acetic acid. After centrifugation of each preparation, proteins in the supernatant fractions were resolved by disc gel electrophoresis into either two or eight bands, respectively. The SDS-solubilized fraction contained spheroidal particles 11 to 44 nm in diameter. When centrifuged until clear, this fraction after dialysis still gave rise to crystal-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The exosporium of B. cereus group spores appears to be assembled concurrent with but independent of the cortex and coat (Ohye and Murrell, 1973). Previous investigations of the content and structure of the exosporium suggest that its assembly is uniform (Gerhardt and Ribi, 1964;Beaman et al, 1971;Ohye and Murrell, 1973;Steichen et al, 2005). The experiments described in this paper, which were designed to Immobilized spores were allowed to germinate and outgrow as described in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The exosporium of B. cereus group spores appears to be assembled concurrent with but independent of the cortex and coat (Ohye and Murrell, 1973). Previous investigations of the content and structure of the exosporium suggest that its assembly is uniform (Gerhardt and Ribi, 1964;Beaman et al, 1971;Ohye and Murrell, 1973;Steichen et al, 2005). The experiments described in this paper, which were designed to Immobilized spores were allowed to germinate and outgrow as described in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Spores of all the B. cereus group species possess an outermost layer, called the exosporium, which is not present on other species, including B. clausii, B. safensis and B. subtilis, among others (Driks, 2002;Traag et al, 2010). The exosporium is comprised of a paracrystalline basal layer which is covered by a hair-like nap layer (Gerhardt and Ribi, 1964;Hachisuka et al, 1966;Gerhardt, 1967;Beaman et al, 1971;Sylvestre et al, 2002;Lai et al, 2003;Steichen et al, 2003;Todd et al, 2003;Giorno et al, 2007;). The exosporium, as the outermost layer of the spores of these species, likely plays important roles in interactions with surfaces in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy has revealed that the exosporium is composed of a paracrystalline basal layer and a hair-like outer layer (Gerhardt and Ribi 1964). The paracrystalline layer has a hexagonal, perforate lattice structure (Beaman et al 1971). In addition to protein components, the native exosporium fraction contained lipid and carbohydrate (Matz et al 1970;Beaman et al 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The paracrystalline layer has a hexagonal, perforate lattice structure (Beaman et al 1971). In addition to protein components, the native exosporium fraction contained lipid and carbohydrate (Matz et al 1970;Beaman et al 1971). Approximately eight protein components were reported to be present in the exosporium, but these were not characterized further (Beaman et al 1971).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation